2014
DOI: 10.1088/0004-637x/784/2/159
|View full text |Cite
|
Sign up to set email alerts
|

THE IMPORTANCE OF JET BENDING IN GAMMA-RAY AGNs—REVISITED

Abstract: We investigate the hypothesis that γ-ray-quiet AGN have a larger tendency for jet bending than γ-ray-loud AGN, revisiting the analysis of Tingay, Murphy & Edwards (1998). We perform a statistical analysis using a large sample of 351 radio-loud AGN along with γ-ray identifications from the Fermi Large Area Telescope (LAT). Our results show no statistically significant differences in jet-bending properties between γ-ray-loud and γ-ray-quiet populations, indicating that jet bending is not a significant factor for… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 74 publications
0
3
0
Order By: Relevance
“…They suggested that the observed polarization behavior may be the result of the jet bending. Jet bending has been observed in a number of AGNs (e.g., Graham & Tingay 2014). In this scenario, an oblique shock could be formed due to the interaction of the jet with the external medium.…”
Section: On the Acceleration Mechanismmentioning
confidence: 99%
“…They suggested that the observed polarization behavior may be the result of the jet bending. Jet bending has been observed in a number of AGNs (e.g., Graham & Tingay 2014). In this scenario, an oblique shock could be formed due to the interaction of the jet with the external medium.…”
Section: On the Acceleration Mechanismmentioning
confidence: 99%
“…The comparison of the jet position angle (PA) on parsec and kiloparsec scales does not suggest the presence of strong viewing angle changes; indeed, Graham & Tingay (2014) report a jet PA of ϕ = 139…”
Section: Radiomentioning
confidence: 99%
“…(Jorstad et al 2001). This paper is the third a series of VLBI observations of southern gamma-ray sources: paper I (Tingay et al 1996) contained first-epoch VLBI images of PKS 0208−512, PKS 0521−365, and PKS 0537−441, and paper II (Tingay et al 1998) included VLBI images of an additional six southern sources and investigated the suggestion that jet bending played an important role in gamma-ray sources-a topic revisited more recently by Graham & Tingay (2014).…”
Section: Introductionmentioning
confidence: 99%